MANAJEMEN PEMBELAJARAN TAHFIDZUL QUR`AN PADA PROGRAM KHUSUS DI MADRASAH ALIYAH SWASTA DARUL HUFFAZ - Heri Soleh; Tamyis; Nurul Hidayati Murtafiah (Journal of Islamic Education and Learning, 2022)
Education in Islam should be managed as well as possible. Management of Islamic education is one way to improve the quality of life of people from backwardness, both morally, materially, and spiritually. Good management will certainly produce good results in accordance with the expected plans and goals. The formulation of the problem in this research are: 1) How is the planning of learning tahfidz Al-Qur'an in a special program at Madrasah Aliyah Swasta Darul Huffaz for the academic year 2021/2022? 2) How is the implementation of tahfidz Al-Quran learning in a special program at Madrasah Aliyah Swasta Darul Huffaz for the 2021/2022 academic year? and 3) How is the evaluation of tahfidz Al-Qur'an learning in a special program at Madrasah Aliyah Swasta Darul Huffaz for the 2021/2022 academic year?. so the objectives of this study are: 1) To find out the planning of learning Al-Qur'an tahfidz in a special program at Madrasah Aliyah Swasta Darul Huffaz Academic Year 2021/2022, 2) To find out the implementation of learning tahfidz Al-Qur'an in a special program at Madrasah Aliyah Swasta Darul Huffaz Academic Year 2021/2022., and 3) To find out the evaluation of learning tahfidz Al-Qur'an in a special program at Madrasah Aliyah Swasta Darul Huffaz for the Academic Year 2021/2022. Based on the formulation and research objectives that the author has described, the method used in this study uses a qualitative descriptive approach. The results of this study found that: 1) Learning Planning uses rote targets prepared by the teacher Tahfidz waka of the curriculum and the head of the madrasa through coordination meetings. Tahfidz Al-Qur'an learning is included in local content subjects., 2) The implementation of learning is carried out in two stages, namely the pre-learning stage and the core learning stage.. 3) Learning evaluation uses an assessment in the form of a rote deposit system. But the implementation time is also like with other subjects, namely by doing daily deposit tests, also by making deposit tests at the end of each semester.